KNOWLEDGE, ATTITUDE, AND PRACTICE ABOUT DENGUE FEVER AMONG UNIVERSITY STUDENTS IN LAHORE, PAKISTAN (The Research of Medical Science Review, 2025)
Objective Of Study: To evaluate the level of awareness among university students regarding dengue transmission, symptoms, and preventive strategies. To assess student perceptions and attitudes towards dengue prevention and control. To examine the preventive practices currently adopted by students to avoid dengue infection.Research Design: This study used a cross-sectional research design to assess knowledge, attitudes, and practices (KAP) related to dengue fever among university students in Lahore. Place & Duration of Study: The study was conducted at selected public and private universities in Lahore, including institutions like Superior University, University of the Punjab, and LUMS. The data collection took place over a period of four months, from November 2024 to February 2025.Material & Methods: A cross-sectional study was conducted among 380 university students in Lahore using a structured questionnaire. Participants were selected through convenience sampling. Data collection occurred from November 2024 to February 2025, and analysis was performed using SPSS version 26 with a significance level of p < 0.05. Results: Out of 380 students, 60% correctly identified dengue symptoms, and 70% were aware of mosquito breeding sites. While 75% believed mosquito nets are effective, only 40% trusted government efforts. In terms of practices, 50% regularly used repellents, but only 35% eliminated standing water. These findings highlight a gap between awareness and actual preventive behavior.Conclusion: This study concluded that while university students in Lahore possess a moderate level of knowledge about dengue fever, there is a clear gap between awareness and actual preventive practices. Many students could identify symptoms and understood transmission, but few consistently applied effective measures such as using repellents or removing standing water. This disconnect highlights the need for more behavior-focused educational interventions. By empowering students with practical knowledge and encouraging active participation in dengue prevention, they can serve as key agents in promoting healthier communities.